Evidence for intermolecular forces involved in ladybird beetle tarsal setae adhesion - Naoe Hosoda (Nature Portfolio, 2021)
Abstract Why can beetles such as the ladybird beetle Coccinella septempunctata walk vertically or upside-down on a smooth glass plane? Intermolecular and/or capillary forces mediated by a secretion fluid on the hairy footpads have commonly been considered the predominant adhesion mechanism. However, the main contribution of physical phenomena to the resulting overall adhesive force has yet to be experimentally proved, because it is difficult to quantitatively analyse the pad secretion which directly affects the adhesion mechanism. We observed beetle secretion fluid by using inverted optical microscopy and cryo-scanning electron microscopy, which showed the fluid secretion layer and revealed that the contact fluid layer between the footpad and substrate was less than 10–20 nm thick, thus indicating the possibility of contribution of intermolecular forces. If intermolecular force is the main physical phenomenon of adhesion, the force will be proportional to the work of adhesion, which can be described by the sum of the square roots of dispersive and polar parts of surface free energy. We measured adhesion forces of ladybird beetle footpads to flat, smooth substrates with known surface free energies. The adhesive force was proportional to the square-root of the dispersive component of the substrate surface free energy and was not affected by the polar component. Therefore, intermolecular forces are the main adhesive component of the overall adhesion force of the ladybird beetle. The footpads adhere more strongly to surfaces with higher dispersive components, such as wax-covered plant leaves found in the natural habitat of ladybird beetles. Based on the present findings, we assume ladybird beetles have developed this improved performance as an adaptation to the variety of plant species in its habitat.